Impact of Breakfast Eating Pattern on Nutritional Status, Glucose Level, Iron Status in Blood and Test Grades among Upper Primary School Girls in Riyadh City, Saudi Arabia - AL-Oboudi, Latifah M. (Pakistan Journal of Nutrition, 2010)
The aim of the study was to examine the effect of breakfast eating pattern (between breakfast consumers and non consumers), on nutritional status (body mass index), glucose level, iron status and test grades (school performance) among Saudi school children (girls). A total of 120 female students aged 9-13.9 years from Riyadh city, Saudi Arabia Participated in this cross-sectional study. A pre-designed questioner was used to collect information on their breakfast eating habits. Body weight and height of the girls were measured and Body Mass Index (BMI) was calculated. Tests for blood Glucose (GLU), Hemoglobin (HG), Hematocrit (HT), Serum Iron (SI), serum ferritin were performed and Total Iron Binding Capacity (TIBC) was calculated. School marks of the previous semester were also collected (used). The results shows that 23.33% of girls ate breakfast only once a week or less often, whereas (40.83%) of the girls ate breakfast daily. Skipping breakfast increased with age. Breakfast skipping was significantly noticed among over weight-obese students compared to lean students, the mean level of HB, HCT, SI, TIBC and ferritin of the girls who ate breakfast regularly was the highest with no significant difference. Regular habit of eating breakfast had beneficial impact on nutritional status.